(untitled) (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Background: Oxidative stress is involved in the pathogenesis of several degenerative diseases. This work studied the in vitro anti-oxidative properties of methanolic extracts of 10 Cameroonian medicinal plants including Autranella congolensis (AC); Beilschmiedia anacardioides(BA); Crossopteryx febrifiga (CF); Cussonia arborea (Cu A); Cyphostema adenaucaule (Cy A); Dissotis longipetala (DL); Lonchocarpus sepium(LS); Nauclea pobeguinii (NP); Pycnanthus angolensis (PA); Picralima nitida (PN) used in folk medicine against various ailments associated with oxidative damages pattern. Method: The extracts were subjected to phytochemical screening to identify major classes of secondary metabolites. Their total contents in phenols, flavonoids were determined; whereas the anti-oxidative and reducing power were evaluated. These extracts were tested for their scavenging activity using DPPH, ABTS, superoxide, hydroxyl and nitric oxide radicals and hydrogen peroxide. The inhibitory effects of extracts against lipid peroxidation were also investigated on rat brain homogenates. Results: The methanolic extracts of CF, DL, LS and AC showed important antioxidant activities and scavenging properties against all radicals system used. The extract of CuA and NP were inactive against hydrogen peroxide. The most potent antioxidant activity was obtained with AC extract, which showed the lowest IC50 value as compared to the standard. The IC50 values of this extract were 7.31±0.25, 5.20±0.35, 42.17±0.60, 77.30±7.41, 32.94±1.32, 9.71±1.07 and 121.59±1.08 Î¼g/ml against ABTS, DPPH, hydrogen peroxide, inhibition of lipid peroxidation, superoxide radical, hydroxyl radical and nitric oxide radical system respectively. These values were found to be comparable to those obtained with the standards. Significant positive correlations were observed between total antioxidant activity with total reducing power (p<0.01; R2=0.8190), total flavonoids (P<0.05; R2=0.6419) and total phenol (P<0.01; R2=0.8643); whereas non-significant correlation was obtained between other systems and the total phenolic constituents. Conclusion: The data generated from this study sustained the use of these medicinal plants in the treatment of various diseases associated with oxidative stress. The potent antioxidant activity of the Autranella congolensis extract and its high content in phenolic constituents are to be taken into the consideration for further phytochemical and biological investigations.